Cepheids as Swiss army knives for Milky Way archaeology - Lemasle, Bertrand; Kovtyukh, Valery; Silva, R. da; Mor, R.; Bono, G.; Figueras, F.; François, P.; Inno, L.; Magurno, D.; Matsunaga, N.; McWilliam, A.; Robin, A. C. (Proceedings of the International Astronomical Union, 2018)
Cepheids are excellent stellar tracers: they are bright enough to be observed even at large distances; their distances can be accurately determined via period-luminosity relations; their spectra contain numerous lines that enable us to derive abundances for many α, iron-peak or neutron-capture elements. Classical Cepheids are yellow supergiants that trace the young populations (⩽ 300 Myr); Type II Cepheids are post Horizontal Branch, low-mass, Population II stars (⩾ 10 Gyr). Both can be used for many purposes in Milky Way archaeology.
Gesehen am 03.09.2019